Process analysis and sensitivity study of regional ozone formation over the Pearl River Delta, China, during the PRIDE-PRD2004 campaign using the Community Multiscale Air Quality modeling system - X. Wang; Y. Zhang; Y. Hu; W. Zhou; K. Lu; L. Zhong; L. Zeng; M. Shao; M. Hu; A. G. Russell (Atmospheric Chemistry and Physics, 2010)
In this study, the Community Multiscale Air Quality (CMAQ) modeling system is used to simulate the ozone (O3) episodes during the Program of Regional Integrated Experiments of Air Quality over the Pearl River Delta, China, in October 2004 (PRIDE-PRD2004). The simulation suggests that O3 pollution is a regional phenomenon in the Pearl River Delta (PRD). Elevated O3 levels often occurred in the southwestern inland PRD, Pearl River estuary (PRE), and southern coastal areas during the 1-month field campaign. Three evolution patterns of simulated surface O3 are summarized based on different near-ground flow conditions. More than 75% of days featured interactions between weak synoptic forcing and local sea-land circulation. Integrated process rate (IPR) analysis shows that photochemical production is a dominant contributor to O3 enhancement from 09:00 to 15:00 local standard time in the atmospheric boundary layer over most areas with elevated O3 occurrence in the mid-afternoon. The simulated ozone production efficiency is 2–8 O3 molecules per NOx molecule oxidized in areas with high O3 chemical production. Precursors of O3 originating from different source regions in the central PRD are mixed during the course of transport to downwind rural areas during nighttime and early morning, where they then contribute to the daytime O3 photochemical production. The sea-land circulation plays an important role on the regional O3 formation and distribution over PRD. Sensitivity studies suggest that O3 formation is volatile-organic-compound-limited in the central inland PRD, PRE, and surrounding coastal areas with less chemical aging (NOx/NOy>0.6), but is NOx-limited in the rural southwestern PRD with aged air (NOx/NOy<0.3).